Recent and future evolution of the stratospheric ozone layer - Dameris, Martin; Loyola , Diego (Springer-Verlag Berlin Heidelberg, 2012)
Since the early 1980s significant depletion of the ozone layer in the stratosphere, in other words the ozone hole, has been observed every year over the South Pole area in Antarctic spring. In the meantime destruction of stratospheric ozone has been detected globally. Emissions of man-made halogenated chemicals play a dominant role in ozone loss. Combined analyses of observations and numerical modeling help to understand the complex interplay of the dynamic and chemical processes involved. Evaluated models provide a base for predicting the future recovery of the ozone layer expected for the middle of this century.